Effects of Mobile Money Services on SME Performance: A Case of Small and Medium Enterprises (SMES) in Embu County - Muema, Festus (University of Embu, 2019)
The study sought to investigate the effect of mobile phone-based money transfer services on Small and Medium Enterprises' financial performance in Kenya. The objectives of this study were; to determine if mobile money services uptake has any effect on SMEs growth through increased sales or savings and loan accessibility, to establish whether Mobile Money Services has led to efficiency in service delivery in the SMEs sector, to find out the contribution of Mobile Money Services to better access to financial information in the SMEs sector in Kenya, convenience and accessibility result in increased SMEs performance and establish if mobile money services are considered reliable by SMEs in Embu county. The study adopted descriptive survey method. A target population of registered SMEs was used and total sample size of23 respondents was picked as representative giving a provision of 15% over and above the desired sample size in the event of non-response on some of the respondents in the sample size. The desired sample size was derived using Mugenda and Mugenda (2003) recommendation. Data was collected using self-administered questionnaires and interview guide. The collected data was analyzed using Statistical package for Social Scientist software. The results of the study were analyzed using descriptive and the results were presented using figures and tables. The findings of the study revealed that there is a positive correlation between SM Es financial performance and business growth, efficiency in service delivery, access to information and convenience and reliability. Development of mobile money transfer services influences the development of market; mobile money transfer services enhance efficiency in service delivery in business; access to information in mobile money transfer services depend on the environment and mobile money transfer services are convenient and reliable. The study highly recommends that SME's should have more user-friendly support services that help SM Goals be compatible with such services.